Cich a chut' diabetika - Svacina, S (Vnitrni lekarstvi, 2007)
Dysfunction of olfactory and gustatory functions can occur in diabetes. Gustatory dysfunction correlates with specific complications of diabetes. Olfactory dysfunction correlates with diabetic macronagiopathy. Gustatory sweating is the most important olfactory and gustatory dysfunction in diabetes. Pathology of olfaction and gustation can play a role in the pathogenesis of diabetes and its complications. Olfaction and gustation could be also a target of diabetes therapy in the future.
Keywords: diabetické neuropatie; Sweating, Gustatory; Taste Disorders; Diabetic Neuropathies; Humans; Olfaction Disorders; poruchy chuti; poruchy čichu; gustatorické pocení; lidé